Environmental status of the Jilantai Basin, North China, on the northwestern margin of the modern Asian summer monsoon domain during Marine Isotope Stage 3. (1st October 2017) - Fan, Yuxin; Wang, Yongda; Mou, Xuesong; Zhao, Hui; Zhang, Fu; Zhang, Fan; Liu, Wenhao; Hui, Zhengchuang; Huang, Xiaozhong; Ma, Jun
Graphical abstract: Highlights: Jilantai sub-depression was continuously occupied by lakes since 85 ka. Dengkou sub-uplift was covered by alternant lakes with sands (44–32.5 and 27.5–13 ka) since 80 ka. Co-existence of lakes and dunes in the entire Jilantai Basin during Marine Isotope Stage 3. Abstract: Two drill cores were obtained from the Jilantai sub-depression (JLT(d)) and the neighboring Dengkou sub-uplift (DK(u)), within a huge, former lake basin in northern China. From an analysis of the lithology and pollen assemblages, combined with radiocarbon dating of extracted pollen and OSL dating of extracted quartz, we concluded the following: JLT(d) was continuously occupied by lakes since 85 ka; however, DK(u), the neighboring sub-uplift, was covered by lakes during 80–74 ka, 50–44 ka, 32.5–27.5 ka and <13 ka, and covered by sand during 44–32.5 ka and 27.5–13 ka. The evidence from lithology and dating results supports the occurrence of lakes on DK(u) during Marine Isotope Stage (MIS) 3. Evidence from shorelines, previously published cores, and the sedimentary and chronological evidence presented in this paper indicate the occurrence of a sub-humid environment, characterized by the occurrence of lakes separated by dunes, in the Jilantai Basin during MIS 3. However, further work is needed to understand the environmental significance of the co-existence of lakes and dunes during MIS 3, although a sub-humid climate background during MIS 3 is supported by well-dated geological archives along the western front of the present-day Asian Summer Monsoon domain and its eastern extensional area.